TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN IPA - Dwi Nugraheni Rositawati; Gregorius Ari Nugrahanta (Prosiding SNFA (Seminar Nasional Fisika dan Aplikasinya), 2018)
Abstract: This research applies a guided inquiry method that is used to improve critical thinking skills in cognitive categories, general and special affective disposition categories and to determine the difference in the proportion of scores of six critical thinking elements in the cognitive category of fifth-grade students in four Kanisius elementary schools in Yogyakarta. The type of research used quantitative research. Critical thinking ability in the cognitive category is known from the results of the pretest and posttest scores which are arranged based on the test essays of a case. Whereas to measure the critical thinking skills of general and special affective disposition categories, a questionnaire with a Lickert scale was used which was filled out by the students. The application of the inquiry method in the science course further enhances critical thinking skills in the cognitive category compared to critical thinking skills in general and special affective disposition categories of fifth-grade students in four Kanisius Elementary Schools in Yogyakarta. There is a difference in the proportion of the increase in the score of six elements of critical thinking in the cognitive category in class V students in four Kanisius Elementary Schools in Yogyakarta. The increase in the six elements can be sorted from the highest to the lowest increase, namely interpretation, analysis, self-regulation, inference, evaluation, and explanation.Abstrak: Penelitian ini menerapkan metode inkuiri terbimbing yang digunakan untuk meningkatkan kemampuan berpikir kritis pada kategori kognitif, kategori disposisi afektif umum dan khusus serta untuk mengetahui perbedaan proporsi skor enam unsur berpikir kritis kategori kognitif siswa kelas V di empat SD Kanisius Yogyakarta. Jenis penelitian yang digunakan adalah penelitian kuantitatif. Kemampuan berpikir kritis pada kategori kognitif diketahui dari hasil nilai Pretest dan posttest yang disusun berdasarkan test essay suatu kasus. Sedangkan untuk mengukur kemampuan berpikir kritis kategori disposisi afektif umum dan khusus digunakan kuesioner dengan skala Lickert yang diisi oleh para siswa. Penerapan metode inkuiri pada matapelajaran IPA lebih meningkatkan kemampuan berpikir kritis pada kategori kognitif dibanding kemampuan berpikir kritis pada kategori disposisi afektif umum dan khusus dari para siswa kelas V di empat SD Kanisius Yogyakarta. Ada perbedaan proporsi kenaikan skor enam unsur berpikir kritis kategori kognitif pada siswa kelas V di empat SD Kanisius Yogyakarta. Kenaikan yang terjadi pada enam unsur tersebut dapat diurutkan dari yang paling tinggi kenaikannya sampai yang paling rendah, yaitu interpretasi, analisis, regulasi diri, inferensi, evaluasi, dan eksplanasi.